PENGARUH PENERIMAAN DAN PENGELUARAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI-PROVINSI DI INDONESIA SEBELUM DAN SESUDAH OTONOMI DAERAH TAHUN 1994-2010 - Kusriyawanto, Kusriyawanto (Katalogis, 2014)
Kusriyawanto. The effects of provincial government revenue and expenditure on economicgrowth before and after the regional autonomy were investigated. The methodology used is panel regression of 28 provinces in Indonesia during 1994-2010. The empirical evidence showed that there is differences in economic growth before and after the regional autonomy were applied. From the revenue side, the regional autonomy has negative effect on economic growth. After the regional autonomy, the provincial GRDP were decrease by 0.11 percent. However, increased in tax, retribution, and non-tax revenue could increasethe GDRP which in turn increase economic growt. The empirical evidence also showed that the provincial dependency toward Central Government Transfer were decrease. From the expenditure side, the regional autonomy has positive effects on economic growth. After the regional autonomy, the provincial GRDP were increase by 0.20 percent. Expenditure on transportation such as for road etc has positive and significant effects on GDRP. While expenditure for education and health have no significant effects on GDRP.